Surgical Treatment of Complex Coarctation of Aorta with Hypoplastic Aortic Arch in Infants - Prokopovych, L.; Golovenko, O.; Truba, Y.; Boyko, S.; Lazorishinetz, V. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The Paper presents the direct experience results of reconstruction of the aortic arch in newborns and infants with coarctation of the aorta (CA) combined with hypoplasia of the arch. In Amosov National Institute of Cardiovascular Surgery were operated 46 children with CA combined with hypoplasia of the arch. For correction hypoplasia of the aortic arch, we have used two methods: in the case of CA and hypoplasia of A and B segments combination, and with the absence of associated congenital heart defects, we have used left posterolateral thoracotomy according with standard method, which permits to make correction and expand adequately hypoplastic segments; in the case of aortic arch hypoplasia completely and with the present of associated congenital heart defects, we have preferred median access using cardiopulmonary bypass (CPB), antegrade cerebral perfusion and one-step CHD correction.